Структури острівного типу з гіперкоординованими атомами - Гребенюк, А. Г. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2022)
Experimental data and the results of theoretical modeling of the spatial structure and chemical properties of isolated particles (molecules and clusters) characterized by the presence of hypercoordinated atoms and the molecular crystals formed by them have been analyzed. Methods of describing the distribution of electron density in molecular crystals and their polymorphism are considered. The influence of the chemical nature of the molecules of binary compounds on their capability to associate and form clusters is described, and the transition from dispersion interaction to coordination bonds in such structures is traced.The review highlights the properties of many dimers, trimers and oligomers of hydrides and halides of chemical elements of different valence, clusters of elemental-organic and coordination (both inorganic and organic nature) compounds, polyhedral structures with non-classical coordination of atoms, in particular, metal carbohedrenes. The results of quantum chemical calculations using the methods of Hartree-Fock (HF), configurational interaction, electron density functional theory (DFT) and second-order Möller-Plesset perturbation theory (MP2) of the spatial structure and energy characteristics of the considered models are discussed. Theoretical results are compared with available experimental data.